Revolutionizing Infrastructure: A Review of Self-Healing Concrete for Longevity and Resilience - Ibrahim, Siti Aida; Mohd Rizal, Muhammad Shazwan Khir; Mohd Aman, Nur Fatin Faridduddin; Othman, Abdullah Ariff Ariffin (Emerging Advances in Integrated Technology, 2025)
A number of characteristics of autogenous and autonomous healing concrete are examined in this review, including their characterization, processes, and performances. It has been discovered that mineral admixtures, fibers, and self-contained methods including shape memory alloys, capsules, and microbial technologies are effective at repairing fractures. This review posits that autonomous procedures exhibit superior efficacy in fracture repair compared to autogenous methods. Furthermore, the selection of self-healing methodologies and agents is significantly influenced by crack geometry and size. Also under investigation are the effectiveness of biomimetic materials, including capsules, shape memory alloys, and self-healing concrete derived from microorganisms. Finally, current research gaps and the scope of prospective research are identified and discussed.